Peran Audit BPK dalam Meningkatkan Transparansi dan Akuntabilitas Keuangan Daerah Provinsi NTT Kota Kupang - Stefani Vanya; Odilia Aftrin; Audy Pasaribu; Karolina Anu; Alberta Ata; Susana Purnamasari Baso (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Strengthening transparency and accountability in regional financial management remains a critical challenge in the implementation of fiscal decentralization in Indonesia, particularly at the local government level. This study aims to analyze the role of the Audit Board of the Republic of Indonesia (BPK) in promoting transparency and accountability in the financial management of the Kupang City Government. Employing a qualitative descriptive approach, the research utilizes secondary data derived from BPK Audit Reports (LHP), Local Government Financial Reports (LKPD), and relevant regulatory documents. Data were analyzed through document review, data reduction, and interpretative analysis to identify patterns of audit findings and follow-up actions. The findings indicate that BPK audits contribute significantly to improving the quality of financial reporting, strengthening internal control systems (SPIP), and enhancing public access to financial information. In Kupang City, audit recommendations have encouraged improvements in asset administration, expenditure effectiveness, and regulatory compliance. Moreover, the level of follow-up on audit recommendations reflects a growing institutional commitment to accountability. This study concludes that BPK audits play a strategic role not only as a supervisory mechanism but also as a catalyst for strengthening good governance and public trust in local financial management.